Pengaruh Non-linear Kompensasi Manajemen dan Aspek Keahlian Dewan Komisaris Terhadap Penghindaran Pajak - Gandy Wahyu Maulana Zulma (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study focuses on the non-linear effect of management compensation and the expertise of the board of commissioners on corporate tax avoidance. This study utilizes secondary data obtained from the Indonesia Stock Exchange with a sample in a manufacturing industry that meets the criteria. Based on the results of sample selection, 345 observation samples were obtained from three years of observation (2017 to 2019). The analysis technique of this study uses regression, and uniquely in this study, the management compensation variable was specifically tested in the quadratic form to test the non-linear effect of management compensation on tax avoidance. The results of this study indicate that there is a non-linear effect between management compensation and tax avoidance. In addition, the aspect of expertise is very important for the board of commissioners to carry out its supervisory function. The expertise of the board of commissioners can encourage management decisions that tend to be more conservative. These findings can contribute to the development of taxation and corporate governance, which provides a new direction to complement previous research findings, especially regarding the non-linear relationship between management compensation and corporate tax avoidance.